Plan de marketing para la empresa Fabrimuebles Pamel en el cantón El Empalme, año 2015. - Pilligua Espinosa, Narcisa Elizabeth (2016)
This marketing plan's main objective is to define the methods and strategies to follow, so that the company Fabrimuebles Pamel belonging to the village of El Empalme to fulfill the main objectives set by the administration thereof; including the actual position is located within the commercial industry of furniture and home furnishings. It was necessary to establish an internal and external analysis, which allowed us to understand in a real way, the situation presented by the company within the active market, also identified the existing problems within the company, which hinder the development of the same face the competition within an industry that has a high growth rate today. Among the difficulties identified more serious is undoubtedly the corporate advertising Fabrimuebles Pamel, which has been little exploited by the administration, leading to the partial lack of business, among the residents of the village of El Empalme, causing is Thus, the gradual decline in sales of products sold in the same; to do a communications plan, which quickly reversed and the current situation progressive design. Undoubtedly the design and implementation of this marketing plan will allow the positioning of the company Fabrimuebles Pamel within the existing active market in Canton El Empalme and surrounding areas and hence the growth in sales of products in it they marketed. Keywords Marketing, Control, Action, Strategy, Sales, Earnings